Applying Bardach and Patashnik’s Policy Concept to Educational Leadership Development Effort in the Developing World - Gregorius Kukuh Nugroho (Litbang STFT Widya Sasana Malang, 2021)
Researchers in developing countries struggle to develop policies that support leadership development in education. Bardach and Patashnik (2016) in their seminal book titled “A Practical Guide for Policy Analysis: The Eightfold Path to More Effective Problem Solving” is a robust literature for high-quality policy. The researcher for this study using the paradigm from Bardach and Patashnik (2016) as a means to advocate Indonesia to build high-quality policy. As policymakers and all level leadership in educational settings work in the developing world contemplate what infrastructure and policy to take when formulating improvement on leadership development, they would do better to base their approach using Eightfold Path by Bardach & Patashnik (2016).